Aljabar Untuk Anak Usia Dini - Lathipah Hasanah; Ika Nurul Amalia; Muthia Ambar Wulan; Baiq Sabilla Berliana; Fathul Habib Sholeh (incrementapedia, 2022)
This paper aims to describe the importance of teaching algebraic content and algebraic thinking skills for early childhood and how the learning strategies are at the early childhood education level. The research method uses library research to understand learning algebraic content and algebraic thinking for early childhood. The results obtained in this study include the application of learning mathematics for children through various creative activities and introducing the concept of arithmetic and geometric concepts. Both of these concepts in teaching early childhood are introduced to several objects in the environment around them so that these mathematical concepts can be understood and understood more deeply by early childhood.